Human resources management in developing learning strategies in the new normal era - Farida Yuliaty (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The purpose of this study was to analyze human resource management in developing learning strategies in the New Normal era, because many learning during the pandemic was found to be ineffective and inefficient, so that students were confused. In this new normal, a human resource management strategy is needed that can be used to monitor. This research method uses a library research approach which is a research method to find and describe some appropriate and relevant research from the topic that the researcher will do. The results of this study indicate that during this pandemic various problems were experienced by various parties. So that HR management is needed to improve learning strategies in the new normal era, namely through efforts, mature readiness, and debriefing both in terms of ICT learning and virtual study habits.